2016
DOI: 10.1089/mab.2016.0022
|View full text |Cite
|
Sign up to set email alerts
|

Specific Detection of Dog Podoplanin Expressed in Renal Glomerulus by a Novel Monoclonal Antibody PMab-38 in Immunohistochemistry

Abstract: Podoplanin (PDPN) is expressed in several normal tissues including podocytes of renal glomerulus, lymphatic endothelial cells (LECs), and type I alveolar cells of lung. PDPN activates platelet aggregation by binding to C-type lectin-like receptor-2 (CLEC-2) on platelets. Many monoclonal antibodies (mAbs) against human PDPN, mouse PDPN, rat PDPN, rabbit PDPN, and bovine PDPN have been established; antidog PDPN (dPDPN) mAbs have not been developed. Herein, we immunized mice with the recombinant proteins of dPDPN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 48 publications
0
44
0
Order By: Relevance
“…2). PMab-48 reacted with lymphatic endothelial cells in immunohistochemistry, (10) although PMab-38 did not, (9) demonstrating that the N-terminal region is a more adequate epitope for detecting dPDPN of lymphatic endothelial cells probably because N-terminus might not be O-glycosylated. (12) In contrast, PMab-38 showed cancer specificity in immunohistochemistry using canine tissues (2) in the same pattern with anti-human PDPN (hPDPN) cancer-specific mAbs, such as LpMab-2 (7,13) and LpMab-23.…”
Section: Figmentioning
confidence: 97%
See 2 more Smart Citations
“…2). PMab-48 reacted with lymphatic endothelial cells in immunohistochemistry, (10) although PMab-38 did not, (9) demonstrating that the N-terminal region is a more adequate epitope for detecting dPDPN of lymphatic endothelial cells probably because N-terminus might not be O-glycosylated. (12) In contrast, PMab-38 showed cancer specificity in immunohistochemistry using canine tissues (2) in the same pattern with anti-human PDPN (hPDPN) cancer-specific mAbs, such as LpMab-2 (7,13) and LpMab-23.…”
Section: Figmentioning
confidence: 97%
“…CHO-K1 cells were transfected with the dPDPN-MAP tag plasmid using Lipofectamine LTX (Thermo Fisher Scientific, Inc., Waltham, MA). (9) CHO/dPDPN cells were cultured in an RPMI 1640 medium (Nacalai Tesque, Inc., Kyoto, Japan), supplemented with 10% heat-inactivated fetal bovine serum (Thermo Fisher Scientific, Inc., Waltham, MA), 100 U/mL penicillin, 100 mg/mL streptomycin, and 25 mg/mL amphotericin B (Nacalai Tesque, Inc.), and incubated at 37°C in a humidified atmosphere of 5% CO 2 and 95% air.…”
Section: Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kan et al reported that PDPN expression in cancer-associated fibroblasts correlates with aggressive behavior in human melanoma, (21) indicating that PDPN in cancer-associated fibroblasts of melanoma tissues might serve as a useful prognostic factor not only in human melanoma but also in canine melanoma. As shown in Figure 2C, PDPN of lymphatic endothelial cells was detected by PMab-38 in melanoma tissues, although lymphatic endothelial cells in normal tissues (18) or squamous cell carcinomas (19) were not stained by PMab-38, indicating that PDPN expression might be upregulated in melanoma, or post-translational modification of canine PDPN might be different between squamous cell carcinomas and melanomas.We recently reported that the PMab-38 epitope is far from the platelet aggregation-stimulating domain of PDPN. However, we have not clarified whether the epitope of PMab-38 includes the post-translational modification.…”
mentioning
confidence: 94%
“…(6,10) We previously developed an anticanine PDPN monoclonal antibody (mAb), (18) which is useful for immunohistochemistry (IHC), flow cytometry, and Western blotting. Recently, we demonstrated that PMab-38 can recognize PDPN of canine squamous cell carcinomas using IHC.…”
mentioning
confidence: 99%